Energy and economic assessment of mixed palm residue utilisation for production of activated carbon and ash as fertiliser in agriculture - Ukanwa, Kalu Samuel; Patchigolla, Kumar; Sakrabani, Ruben (Taylor and Francis, 2021)
he resultant residues after thermal processes can be reused in the form of activated carbon (AC) production or used for soil amelioration. However, the economic and energy optimisation of the waste revaluation process is necessary for the prediction of technology requirements, investment boundaries and cost–benefit analysis. Mass, energy and cost estimation of the entire process were systematically executed relative to equipment sizing and type of product, as major factors in the evaluation. The economic analysis and process optimisation were quantified and evaluated with the Aspen Plus economy and an SPSS statistical tool for economic analysis. Simulation results were concomitant with economic analysis to determine the approximate annualised return on investment, profitability index and payback period, using optimised variables in the process. The four processes examined: process scenario 1–4 (pyrolysis, gasification, combustion and combined) have 16, 17, 14 and 17.2% return on investment for the 8.5, 8.2, 9.8 and 8-year payback period, respectively. The results provide a technology assessment and economic guide for investors and policymakers among others. This work is also useful for researchers in achieving the goal of efficient biomass utilisation. Palm waste ash as a potential alternative to chemical fertiliser, especially for the treatment of ultisol and acidic soils, were evaluated and it was confirmed that it is a good alternative to typical inorganic fertiliser. Finally, the results indicate that using such wastes in the AC market is a viable business option, though with high initial capital investment even though palm waste ash can be produced locally.
Keywords: Activated carbon; biomass; palm waste ash; techno-economic analysis; thermal process